Protecting, managing and bending boundaries: a biomedicalization perspective on Swedish youth clinics' responses to mental (ill) health - Isabel Goicolea; Maria Wiklund; Ida Linander; Linda Richter Sundberg (BMC, 2022)
Abstract Background Sweden has provided around 300 youth clinics (YCs) to address the health needs of young people since the 1970s. During the last few years, and as part of an effort to strengthen mental healthcare for young people, YCs' role in the provision of mental healthcare has been widely debated. With such debates as background, the aim of this study is to analyse Swedish YCs' responses to the mental (ill) healthcare needs of young people, from the perspective of national level stakeholders. Methods We used thematic analysis of interviews with eight national level stakeholders in the field of youth mental health in Sweden. Building upon the concept of biomedicalization we examined the discourses on mental (ill) health, healthcare and youth that such responses reproduce. Results YCs engage in the three simultaneous, but at times contradictory, responses of protecting, managing and bending boundaries. Remaining true to their mission as a health-promotion service compels them to protect their boundaries and limit the type of mental health issues they address. However, the perceived malfunctioning of specialized services has led them to bend these boundaries to allow in more young people with severe mental health problems. Caught between protecting and bending boundaries, the response of managing boundaries to decide who should be allowed in and who should be sent elsewhere has emerged as a middle-way response. However, it is not free from conflicts. Conclusion Building upon the concept of biomedicalization, this study poses two questions. The first relates to whether it is possible to support young people and their health without reinforcing discourses that represent young people as collectively at risk, and if so how this can be done. The second relates to the provision of mental healthcare for young people, and the need to identify conditions for integrating diagnosis and treatment within YCs, without hindering their holistic and youth-centred approach.